The Influence of Teleworking on Performance and Employees’ Counterproductive Behaviour. - Marcela-Sefora Nemțeanu; Dan-Cristian Dabija; Liana Stanca (Amfiteatru Economic)
The new social context brought about by the COVID-19 pandemic has generated significant changes in the work of employees. Social distancing and isolation have imposed the adoption of teleworking in most cases. Teleworking existed before the COVID-19 pandemic, and was considered a facilitator of job flexibility, thus increasing employees’ autonomy in their work. This paper aims to identify how teleworking, through its dimensions (teleworking autonomy and interaction reduction) influences self-regulatory capacity, professional isolation, task performance, contextual performance, and counterproductive work behaviours. The data were collected from 641 respondents, namely Romanian employees, who operated by teleworking. The theoretical model and relation between the constructs were tested with the aid of structural equation modelling in SmartPLS. The interaction reduction in the context of teleworking significantly, positively, and strongly influences professional isolation, and to a lesser extent, but significantly nonetheless, counterproductive work behaviour and employee self-regulatory capacity. The research originality lies in expanding the theoretical contributions regarding teleworking theory by proposing a new teleworking scale based on teleworking autonomy and interaction reduction. It also contributes to the development of Self-regulatory Theory and Social Exchange Theory. From a managerial perspective, it highlights the importance of the dimensions of teleworking for the employer, as well as the effects of teleworking on task performance and contextual performance in the COVID-19 pandemic, offering helpful solutions to employers in the identification of viable solutions for the improvement of employee outcomes, and for the reduction of counterproductive work behaviour